2015
DOI: 10.1164/rccm.201412-2230oc
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Mucus Concentration (Hydration) to Mucus Osmotic Pressure and Transport in Chronic Bronchitis

Abstract: Rationale: Chronic bronchitis (CB) is characterized by persistent cough and sputum production. Studies were performed to test whether mucus hyperconcentration and increased partial osmotic pressure, in part caused by abnormal purine nucleotide regulation of ion transport, contribute to the pathogenesis of CB.Objectives: We tested the hypothesis that CB is characterized by mucus hyperconcentration, increased mucus partial osmotic pressures, and reduced mucus clearance.Methods: We measured in subjects with CB as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
159
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 135 publications
(173 citation statements)
references
References 54 publications
12
159
2
Order By: Relevance
“…Our studies show that exposure to IFN-␥ causes inhibition of hypotonic stress-induced ATP release by ϳ78%, which would impair proper mucociliary clearance. Our data fit well with data from a recent publication showing that smokers and patients with chronic bronchitis have not only decreased ATP concentrations in their airway surface liquid but also ATP levels below the ones needed for signaling (39).…”
Section: Discussionsupporting
confidence: 89%
“…Our studies show that exposure to IFN-␥ causes inhibition of hypotonic stress-induced ATP release by ϳ78%, which would impair proper mucociliary clearance. Our data fit well with data from a recent publication showing that smokers and patients with chronic bronchitis have not only decreased ATP concentrations in their airway surface liquid but also ATP levels below the ones needed for signaling (39).…”
Section: Discussionsupporting
confidence: 89%
“…Therefore, we examined the nucleotide content in sputum samples (believed to reflect secretions from the large airways) [38] obtained from CF patients with moderate or severe lung disease and from healthy control subjects. As indicated in Table 1, CF patients exhibited decreased pulmonary function (assessed as forced expiratory volume, FEV1% predicted) and increased (but broadly spread) number of neutrophils in sputum.…”
Section: Resultsmentioning
confidence: 99%
“…121 For example, a recent study found that the total solids content was reduced in induced versus bronchoscopy-derived (i.e., undiluted) samples from the same patients. 122 In contrast, spontaneously expectorated sputum can be used with negligible concern of sample dilution. However, spontaneously expectorated samples are generally produced by patients who have a respiratory disease, such as CF, COPD or asthma.…”
Section: Mucus Samples Used To Assess Mucus Barrier Properties Sourcementioning
confidence: 99%